Factors of supervisory board efficiency in municipally owned enterprises (Economic and Political Thought, 2017)
The main aim of this article is to present the results of empirical researchinto the factors and their impact on the efficiency of supervisory boards inmunicipally owned companies. The first part defines the concept of a municipallyowned company. Next, the importance and role of a supervisory boardin a company is characterised. In the second part, the concept of supervisoryboard efficiency is formulated and factors determining it are identified. Theauthor also presents the results of his study into the impact of selected factorson the efficiency of supervisory boards of municipally owned companiessurveyed. The conclusions are based on the study of literature and a questionnairecompleted by three groups of respondents.